Development and serology based efficacy assessment of a trivalent foot-and-mouth disease vaccine. Issue 32 (6th July 2020) - Al Amin, Md.; Ali, M. Rahmat; Islam, M. Rafiul; Alam, A.S.M. Rubayet Ul; Shill, Dipok Kumer; Rahman, M. Shaminur; Siddique, Mohammad Anwar; Sultana, Munawar; Hossain, M. Anwar
Highlights: Three vaccine strains were selected from circulating FMDVs in Bangladesh. The vaccine strains showed strong antigenic relationship with FMDVs of Bangladesh. A new trivalent FMD vaccine was developed using the selected vaccine strains. The vaccine elicited antibody titers expected to confer protection in cattle. The vaccine is suitable to control FMD in Bangladesh and its neighboring countries. Abstract: Foot-and-mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals throughout the world. The endemicity of this disease in Bangladesh has been causing high economic loss and an impediment to the full potential surge of livestock industries. In Bangladesh, vaccination using imported or locally produced FMD vaccines is the existing practice of controlling the disease, although vaccine failure cases are very common. Hence, to address the problem, the present study was envisaged to develop an effective FMD vaccine tailored to the circulating indigenous foot-and-mouth disease virus (FMDV) strains. Three local circulating FMDVs O/BAN/TA/Dh-301/2016 (MK088170.1 ), A/BAN/CH/Sa-304/2016 (MK088171.1 ) and Asia1/BAN/DH/Sa-318/2018 (MH457186.1 ) isolates were selected as vaccine strains based on recent epidemiology, genetic and antigenic analyses. These serotype O, A and Asia1 vaccine strains showed strong antigenic relationship (r1 > 0.3) with 100% to 75% of the respective circulating viruses. The candidate viruses were successfully inactivated by 3.0 mM binary ethylenimine within 7–10 h after the onset of inactivation. Extrapolation of inactivation kinetics confirmed < 1 log10 TCID50 in a 10000-liter batch liquid preparation after 24 h inactivation cycle. The inactivated virus particles were significantly ( p  < 0.05) concentrated and the trivalent vaccine was formulated using 6 µg per dose per serotype antigen payload. The trivalent vaccine was administered in divided doses in different groups of cattle. All doses of the vaccine elicited significantly ( p  < 0.05) higher levels of antibodies as early as 14-day post-vaccination (dpv) and peak antibody titers were achieved in 28 dpv. The 'full dose' (6.0 µg per dose per serotype) vaccine elicited antibody titers expected to confer protection in 100% cattle of the respective group and maintained such level of antibodies beyond 180 dpv. Thus, the trivalent FMD vaccine prepared with 6.0 µg antigen per dose per serotype of the selected candidate viruses will confer protection against circulating FMDVs of Bangladesh and its neighboring countries.